Asymmetric Propagation Delay-Aware TDMA MAC Protocol for Mobile Underwater Acoustic Sensor Networks - A-Ra Cho (Applied Sciences, 2018)
The propagation delay in mobile underwater acoustic sensor network (MUASN) is asymmetric because of its low sound propagation speed, and this asymmetry grows with the increase in packet travel time, which damages the collision avoidance mechanism of the spatial reuse medium access control (MAC) protocols for MUASN. We propose an asymmetric propagation delay-aware time division multiple access (APD-TDMA) for a MUASN in which periodic data packet transmission is required for a sink node (SN). Collisions at the SN are avoided by deferring data packet transmission after reception of a beacon packet from the SN, and data packets are arrived at the SN in a packet-train manner. The time-offset, which is the time for a node to wait before the transmission of a data packet after reception of a beacon packet, is determined by estimating the propagation delay over two consecutive cycles such that the idle interval at the SN is minimized, and this time-offset is announced by the beacon packet. Simulation results demonstrate that the APD-TDMA improves the channel access delay and the channel utilization by approximately 20% and 30%, respectively, compared with those of the block time bounded TDMA under the given network conditions.